Magneto-structural correlations in oxalate-bridged Sr(ii)Cr(iii) coordination polymers: structure, magnetization, X-band, and high-field ESR studies. Issue 11 (21st February 2018) - Androš Dubraja, L.; Jurić, M.; Popović, J.; Pajić, D.; Krupskaya, Y.; Kataev, V.; Bűchner, B.; Žilić, D.
Abstract : Magneto-structural correlations in 1D oxalate-bridged Sr(ii )Cr(iii ) coordination polymers with two crystallographically and magnetically non-equivalent Cr(iii ) ions are studied by HF-ESR spectroscopy. Abstract : The results of high-field electron spin resonance (HF-ESR) spectroscopy on the title 1D coordination polymers at frequencies up to 415 GHz, supported by X-ray diffraction, thermal, magnetic susceptibility, and X-band (10 GHz) ESR studies, are presented. The heterometallic compounds {SrCr2 (phen)2 (C2 O4 )4 }·H2 O (SrCrPhen) and {SrCr2 (bpy)2 (C2 O4 )4 (H2 O)}·5H2 O (SrCrBpy) (phen = 1, 10-phenanthroline, bpy = 2, 2′-bipyridine) were synthesized. Structural analysis revealed double oxalate-bridged zigzag Sr–Cr chains while magnetic susceptibility studies showed paramagnetic behaviour of the complexes. HF-ESR spectroscopy data were analysed with a relevant spin-Hamiltonian, yielding the g, D and E parameters of the Cr(iii ) ions. Both complexes showed small magnetic easy-axis type anisotropy with | D | ∼ 1 K; SrCrBpy has uniaxial anisotropy while SrCrPhen has biaxial anisotropy. HF-ESR studies have enabled us to establish rational magneto-structural correlations and revealed significant differences between very similar crystal structures. Additionally, the ability of SrCrPhen and SrCrBpy to be single-source precursors for the formation of Sr–Cr oxides was investigated.